A detrending-extracting-zooming-based speed measurement method for hermetic reciprocating compressor. (June 2020) - Jin, Huaqiang; Sun, Zhe; Gu, Jiangping; Huang, Yuejin; Wang, Xinlei; Zhang, Qinjian; Shen, Xi
Highlights: The generation mechanism and influence law of pressure pulsation is analyzed. A new DEZ-based speed measurement method for hermetic compressor is proposed. The maximum error of the method is smaller than ±1 rpm at 2 s sampling time. Abstract: The rotational speed is an important parameter of hermetic compressor, which has a great significance on refrigeration capacity, power consumption, and coefficient of performance. However, the change of load condition causes the moving parts of compressor and the refrigerant to operate unsteadily, which leads to large deviation when the traditional speed measurement method is used. To solve this issue, this work proposes a Detrending-Extracting-Zoming (DEZ) method to measure the rotational speed of hermetic reciprocating compressor. A three-dimensional fluid structure interaction (FSI) model is set up to reveal the influence law of pressure pulsation at different operating speeds. On this basis, it can be found that the trend component and harmonic components of pressure pulsation affect the calculation of rotational frequency. Based on the above mechanism, the DEZ first eliminates the trend component of pressure pulsation, then extracts the feature component, and finally calculates the exact rotational frequency by spectrum zooming. The results of simulation and experiment show that the proposed measurement method is reliable under different load conditions, and the maximum error is smaller than ±1 rpm at 2 s sampling time. The key scientific contribution of this paper is providing a rotational frequency calculation method for unstable pressure signal, which can offer universal references to the operating state detection in hermetic reciprocating machines, such as fuel engines and air compressors.